Anterior Clinoid Metastasis as First Presentation of a Signet Ring Cell Carcinoma: An Intriguing Diagnosis - d'Avella, Elena; Guadagno, Elia; Ugga, Lorenzo; Solari, Domenico; Cavallo, Luigi Maria (Journal of Neurological Surgery Reports, 2020)
Background We report an extremely unusual case of anterior clinoid process (ACP) metastasis as the first presentation of a signet ring cell carcinoma.Case Description A 54-year-old female patient presented with right-sided visual disturbances due to optic nerve compression from a computed tomography (CT)-identified right anterior clinoid bone lesion. Contrast-enhanced magnetic resonance imaging showed an extra-axial, well-bordered enhancing mass extending from the right ACP toward the inner lumen of the optic canal. Pterional approach was adopted to remove the lesion and decompress the optic canal. Histological examination demonstrated a metastasis from a signet ring cell carcinoma. Postoperative CT showed near-total resection of the tumor and decompression of the optic canal. Visual defect remained unchanged.Conclusion Metastasis should be considered in the differential diagnosis of the ACP lesions. The early suspicion and identification of this extremely rare pathological entity can be helpful for the prompt management of patients, especially in the absence of any other signs of oncological diseases.
Keywords: anterior clinoid process; metastasis; signet ring cell carcinoma